Design and Development of a Smart Voice Reminder Device - Oh, Tick Hui; Pang, Shen Yee; Lee, Jacob Daryl Yuon Ee (International Journal of Integrated Engineering, 2024)
During the COVID-19 pandemic period, an average student receives more assignments from their teachers while taking online classes. It can be challenging for these young minds to keep track of every assignment’s deadline on top of the various online classes that require their attendance and punctuality. So, to prevent the students from missing any of their online classes and assignment submission, a solution more than just a calendar’s reminder is required as many primary school students might not have access to smartphones. Hence, a voice reminder device is proposed in this paper for this purpose. Raspberry Pi 4 is used to build this device, along with a Python-based program to connect it to the Google Calendar server. The system’s speech recognition is done using a Python speech recognition package. The system uses the Google Cloud Speech API to translate the user’s speech input into a text format that the system can understand. The information required to produce the user-specified event is then extracted along with the activation word, all from the user’s text. The system then saves the event into Google Calendar, using the Google Credentials.json file as its destination file after extracting all the important data. The user can add, edit, or delete any previously established event using the Google Calendar from any location as long as the device is online. It can also generate a timetable through voice command. Other notable usage of this device includes keeping elderlies with Alzheimer’s disease on track with their important tasks like scheduled medication and medical follow-ups. The prototype managed to achieve a rather high accuracy rate of 85.6% through its speech recognition function.